1996
DOI: 10.1002/(sici)1097-0320(19961201)25:4<388::aid-cyto11>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Observation of single‐cell fluorescence spectra in laser flow cytometry

Abstract: We report the first demonstration of directly recording fluorescence spectra of single cells in flow cytometry. An intensified, 512-element photodiode array was used in conjunction with a dispersing prism to capture the fluorescence emission spectra of Coulter ImmunoCheck calibration beads and Dictyostelium discoideum spores stained with the indocarbocyanine derivative CY3, fluorescein isothiocyanate, or R-phycoerythrin. The demonstration was made feasible by enhancing the signal-to-noise ratio of the detectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 0 publications
0
20
0
Order By: Relevance
“…Modifications to lasers and detectors can also be used to enhance the discriminatory power of flow cytometry. Gauci et al [50] demonstrated the use of spectral fingerprinting, a technique to determine spectral properties of particles at tens to hundreds of wavelengths simultaneously. Particle types are recognised by reference to previously assigned optical fingerprints.…”
Section: Future Prospectsmentioning
confidence: 99%
“…Modifications to lasers and detectors can also be used to enhance the discriminatory power of flow cytometry. Gauci et al [50] demonstrated the use of spectral fingerprinting, a technique to determine spectral properties of particles at tens to hundreds of wavelengths simultaneously. Particle types are recognised by reference to previously assigned optical fingerprints.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The IPDA is a solid-state diode array coupled to an image intensifier via a fiber-optic bundle. With the image intensifier as an amplifier for photons, a gain of 3000 to 9000 is typically obtained, thus the signal-tonoise ratio of the IPDA detector is significantly higher than that of the PDA and the IPDA is thus highly sensitive under low-light conditions [58,59]. In comparison, the CCD has extremely low noise, generally under 5 e-and has a dark current less than 1e-per hour if properly cooled, and so is commonly used without intensification in this application [51,57].…”
Section: Instrumentation and Designmentioning
confidence: 99%
“…Neural networks can be trained to recognise sub‐populations of microorganisms from previous data to examine and sort aquatic microbes [171]. Spectral fingerprinting can be used to determine the spectral properties of particles at hundreds of wavelengths simultaneously [172] and lectins can help to improve discrimination of cells from abiotic particles [173]. The exposure of front‐line soldiers or civilian populations to biological warfare agents needs extremely rapid detection.…”
Section: Perspectivesmentioning
confidence: 99%